“How” is more important than “how much” for game possession in elite northern hemisphere rugby union - Ungureanu, Alexandru Nicolae; Brustio, Paolo Ricardo; Mattina, Luca; Lupo, Corrado (Biology of Sport, 2019)
The present study aimed to analyse technical and tactical aspects of rugby teams competing in the 2016/17 PRO12 Championship (12 professional club teams from Wales, Scotland, Italy, and Ireland) according to: margin of victory (close and balanced games, 1–9 and 10–26 points of difference in final score, respectively), ranking position [the four best placed clubs from each nation (the 1st–4th team) and the three following ranked clubs (the 5th–7th team)], and game outcome and ranking combined (winning and losing performances in the 1st–4th and 5th–7th team subgroups). One hundred and thirty-two games were analyzed according to 20 key performance indicators. A non-parametric approach was applied to evaluate differences (p≤0.05) between teams. In close games, winning teams reported less possession (p=0.039), defended more (tackles made, p=0.039), and carried the ball less than losing counterparts (p=0.05), whereas in balanced games, winning teams were found to be much better than losers in “tries for” (p<0.0001) as well as “tries against” (p<0.0001), and “clear breaks” (p=0.0003). The teams of the 1st–4th subgroups were found to be more oriented to provide a solid defence than the 5th–7th winning teams, which were more offensive oriented (possession, p=0.01; gain line carries, p=0.001; passes, p<0.0001). Finally, a similar scenario to that of balanced games emerged for winning and losing performances in the 1st–4th and 5th–7th team subgroups. Coaches and physical trainers of elite northern hemisphere rugby union teams should be aware that successful performances mainly consist of a strong defence, tackling, scrumming, breaking the defensive line and high occurrences of possessions during the attacking phase.